Effect of honeycomb bulkheads on uniaxial undrained bearing capacities of wide-shallow bucket foundation. Issue 2 (September 2019) - Wang, Qingshan; Cao, Yongyong; Han, Xun; Li, Wenxuan
Abstract: In order to study the effect of honeycomb bulkheads on uniaxial undrained bearing capacities of wide-shallow bucket foundation, the finite element models of bucket foundations with and without bulkheads on soft ground were established respectively. A large number of 3D finite element analyses have been performed to obtain uniaxial bearing capacities of the two foundations with different embedment ratios and soil shear strength heterogeneity by using displacement control method. The results show that, for homogenous clay, all the vertical, horizontal and moment bearing capacities of the wide-shallow bucket foundation are not affected by the honeycomb bulkheads. For non-homogenous clay, the moment bearing capacity of the wide-shallow bucket foundation is obviously affected by the honeycomb bulkheads, while the effect for improving the vertical and horizontal bearing capacity of the bucket foundation can be neglected. For the convenience of designers reference, simplified calculation equations for undrained bearing capacities are fitted according to the finite element results.